Perbandingan Efek Pemberian Emulsi Kedelai dan Emulsi Tempe Terhadap Hitung Limfosit Total pada Tikus Putih yang Telah Diberi Prednison - Rizka Bekti Nurcahyani; Imelda T Pardede; Huriatul Masdar (Fakultas Kedokteran Universitas Riau, 2011)
Adequate nutrition is one of important factors in immunodeficiency repairment. Soybean and tempeh contains proteins,zinc, ferrum, vitamins and isoflavon. Fermentation in tempeh makes it having better nutrients digestion and absorptionthan soybean. The objective of this study was to compare the effects of soy and tempeh emulsions on total lymphocytecount in rats treated with prednisone. The test was done on 24 male white rats divided into four groups. Group A wasgiven distilled water and group B, C and D had prednisone 2.5 mg/day for 6 days. After that, group A and B werecontinued having distilled water while groups C or D was fed with soy or tempeh emulsion 0.71 mL/day for 10 days,respectively. The results shown that soy and tempeh emulsion could increase total lymphocyte count significantly (p <0,05) but there was no significant difference of total lymphocyte count between soy and tempeh emulsion groups (p >0,05).